CRISPR-TSKO: A Technique for Efficient Mutagenesis in Specific Cell Types, Tissues, or Organs in Arabidopsis. Issue 12 (27th September 2019) - Decaestecker, Ward; Buono, Rafael Andrade; Pfeiffer, Marie L.; Vangheluwe, Nick; Jourquin, Joris; Karimi, Mansour; Van Isterdael, Gert; Beeckman, Tom; Nowack, Moritz K.; Jacobs, Thomas B.
Abstract : CRISPR-TSKO (tissue-specific knockout) induces somatic mutations and enables the phenotypic analysis of context-specific gene function. Abstract: Detailed functional analyses of many fundamentally important plant genes via conventional loss-of-function approaches are impeded by the severe pleiotropic phenotypes resulting from these losses. In particular, mutations in genes that are required for basic cellular functions and/or reproduction often interfere with the generation of homozygous mutant plants, precluding further functional studies. To overcome this limitation, we devised a clustered regularly interspaced short palindromic repeats (CRISPR)-based tissue-specific knockout system, CRISPR-TSKO, enabling the generation of somatic mutations in particular plant cell types, tissues, and organs. In Arabidopsis ( Arabidopsis thaliana ), CRISPR-TSKO mutations in essential genes caused well-defined, localized phenotypes in the root cap, stomatal lineage, or entire lateral roots. The modular cloning system developed in this study allows for the efficient selection, identification, and functional analysis of mutant lines directly in the first transgenic generation. The efficacy of CRISPR-TSKO opens avenues for discovering and analyzing gene functions in the spatial and temporal contexts of plant life while avoiding the pleiotropic effects of system-wide losses of gene function.